P377 Changes over time in the Lémann Index and the Inflammatory Bowel Disease-Disability Index in patients with Crohn's disease. (30th January 2023) - Wils, P; Cartier, L; Azahaf, M; Hambli, S; Branche, J; Gérard, R; Desreumaux, P; Louvet, A; Nachury, M
Abstract: Background: Crohn's disease (CD) is a progressive, transmural disorder that leads to intestinal damage (fistula, abscesses, stenosis) and worsens the patient's quality of life. The Lémann Index (LI, assessing cumulative bowel damage in CD) and the Inflammatory Bowel Disease-Disability Index (IBD-DI) have recently been validated. The objective of the present study was to assess changes over time in the LI and the IBD-DI and to identify factors associated with these changes. Methods: In a cohort of 130 patients with CD being followed up prospectively at Lille University Hospital (Lille, France), the LI and the IBD-DI were evaluated first in 2016 (assessment #1, results previously published) and then again between September 2020 and October 2021 (assessment #2). Factors associated with the differences in the LI and IBD-DI were probed with a Mann-Whitney test or a bivariate analysis of variance. Survival curves for the progression of CD (surgery, drug-related events) were plotted according to the Kaplan-Meier method. Spearman's coefficient was calculated as a guide to the strength of the correlation between the LI and the IBD-DI. Results: 101 patients were included. More than half of the included patients had a long-standing disease (>15 years), 35% had ano-perineal involvement and 56% had a history of resection. Clinical activity was reported in 40% of patients at assessment#2. The median time interval between the two evaluations was 4.2 years. The LI (assessed in 61 patients) did not change significantly (median: 9.6 at #1 vs. 9.3 at #2; p = 0.14). The LI increased for 16 patients (26%), decreased for 26 (43%) and was stable for 19 (31%). Persistent clinical activity was the only factor significantly associated with worsening of the LI (p=0.01). A LI >7.9 was not associated with CD progression. The IBD-DI score (assessed in 98 patients), decreased significantly over time (median: 23.2 at #1 vs. 21.4 at #2; p = 0.006). The IBD-DI decreased for 59 patients (60.2%), increased for 37 (37.8%) and was stable for two (2%). Factors associated with improvement in the IBD-DI were younger age at diagnosis, a longer time interval before initiation of the first biologic, drug optimization, and exposure to combination therapy. There was no correlation between LI and the IBD-DI (r 0.125, p=0.27). Conclusion: This is the first cohort study assessing changes over time in both the LI and the IBD-DI in CD patients. After more than 4 years of follow-up, the LI appeared to be stable and the IBD-DI decreased, without correlation between the indices. Persistent clinical activity was associated with worsening LI reinforcing the interest in monitoring these patients.